2015
DOI: 10.1589/jpts.27.491
|View full text |Cite
|
Sign up to set email alerts
|

The influences of position and forced respiratory maneuvers on spinal stability muscles

Abstract: [Purpose] The purposes of this study were to investigate the influences of position on %MVIC of spinal stability muscles to establish for the most effective breathing pattern for activation of spinal stability muscles in order to provide an additional treatment method for use in spinal stability exercise programs. [Subjects and Methods] Thirty-three healthy subjects performed quiet breathing and four different forced respiratory maneuvers (FRM); [pursed lip breathing (PLB), diaphragmatic breathing (DB), combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Although the body may respond differently depending on the intensity, nature, and duration of the stressor, as well as several internal factors of the individual who experience it [84,85], body sway is a highly sensitive action and is affected by stability muscles. The respiratory muscles act as one of the spinal stability muscles [86] and optimize postural sway [68,73,87]. Studies have reported that the diaphragm and abdominal muscles produce a hydraulic effect that aids spinal stabilization by stiffening the lumbar spine with increased intra-abdominal pressure in the abdominal cavity [88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the body may respond differently depending on the intensity, nature, and duration of the stressor, as well as several internal factors of the individual who experience it [84,85], body sway is a highly sensitive action and is affected by stability muscles. The respiratory muscles act as one of the spinal stability muscles [86] and optimize postural sway [68,73,87]. Studies have reported that the diaphragm and abdominal muscles produce a hydraulic effect that aids spinal stabilization by stiffening the lumbar spine with increased intra-abdominal pressure in the abdominal cavity [88].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the respiratory muscles are important in providing stability to minimize unwanted movements during shooting, albeit with a different mechanism [42]. Some reports show that an increase in the strength and endurance of these muscles might increase spinal stability [86,89].…”
Section: Discussionmentioning
confidence: 99%
“…The diaphragm, the principal muscle of respiration, has been reported to act as one of the spinal stability muscles, and the IO, EO, and PFM are also activated to increase respiratory capacity with the diaphragm. The spinal stability provided by these muscles is generated from their co-contraction, which increases IAP; these muscles also function as respiratory muscles by increasing their activities when respiratory demand increases 11 ) . The present study examined the effect of contraction of the PFM (act as respiratory muscles or stabilize the trunk) on respiratory muscle activity and vital capacity.…”
Section: Discussionmentioning
confidence: 99%
“…No que diz respeito às amostras dos estudos descritos nas tabelas I e II, foram avaliados indivíduos de ambos os sexos, eutróficos [1,3,7,8,[11][12][13][14][15][16][17] e com dor lombar [3,5,7,11,13,17]. A idade da população estudada variou entre 18 e 71 anos, e o tamanho amostral entre 5 e 150 indivíduos, resultando em um total de 421 indivíduos.…”
Section: Figura 1 -Fluxograma De Triagem E Seleção Dos Estudosunclassified